Pengaruh Online Customer Review, Pengetahuan Produk, dan Kualitas Produk Terhadap Keputusan Pembelian Produk Scarlett Whitenning pada Mahasiswa Universitas Pembangunan Nasional Veteran Jawa Timur - Banis , Achniatuzzahra; Dermawan, Rizky (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of online customer reviews, product knowledge, and product quality on the decision to purchase scarlett whitening products for students at the "Veteran" National Development University, East Java. The population in this study were students of the Faculty of Economics and Business UPN "Veteran" East Java with a total sample of 98 respondents. The data collection method in this study uses a survey method and uses partial least squares as a data analysis tool. From the results of the study it was found that online customer reviews, product knowledge and product quality have a major influence on the decision to purchase scarlett whitening products, which means that the better the reviews, product knowledge, and also the quality of scarlett whitening products, the better the student's decision to make a purchase..